Proceedings of the ANSO-PAS-MAAP Conference on Epidemic and Pandemic Preparedness: Proceedings of the ANSO-PAS-MAAP Conference - Iqrar, Irum; Ali, Muhammad; Shinwari, Zabta Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
An EPIDEMIC is a disease that affects many people within a community, population, or region. ENDEMIC is something that belongs to a particular people or country. A PANDEMIC is an epidemic that’s spread over multiple countries or continents. Epidemics and pandemics are some of the leading threats to global health security. They not only affect people’s health and well-being, but they can also have a massive impact on livelihoods and entire societies too. Pandemics can cause sudden, widespread morbidity and mortality as well as social, political, and economic disruption. The world has endured several notable pandemics, including the Black Death, Spanish flu, and human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS). Most new pandemics have originated through the “zoonotic” transmission of pathogens from animals to humans, and the next pandemic is likely to be a zoonosis as well. Zoonoses enter human populations from both domesticated animals (such as farmed swine or poultry) and wildlife. Many historically significant zoonoses were introduced through increased human-animal interaction following domestication, and potentially high-risk zoonoses (including avian influenzas) continue to emerge from livestock production systems. Some pathogens (including Ebola) have emerged from wildlife reservoirs and entered human populations through the hunting and consumption of wild species (such as bushmeat), the wild animal trade, and other contacts with wildlife. Spending and costs specifically associated with pandemic preparedness and response efforts are poorly tracked. There is no widely accepted, consistent methodology for estimating the economic impacts of pandemics. To highlight strategies to combat pandemics, a three-day ANSO-PAS-MAAP Conference on Epidemic and Pandemic Preparedness was jointly organized by the Pakistan Academy of Sciences (PAS), Alliance of International Science Organization (ANSO), and MonbukagakushoMEXT Alumni Association of Pakistan (MAAP) organized a three-day ANSO-PAS-MAAP Conference on “Epidemic and Pandemic Preparedness” from December 5 - 7, 2022 in the Pakistan Academy of Sciences, Islamabad. In total, 31 lectures were delivered at the ANSOPAS-MAAP Conference by leading experts in five technical sessions focused on the surveillance and preparedness against global Pandemics and epidemics. Of these, seven (07) lectures were presented by international speakers and twenty-six (26) lectures were presented by Pakistani speakers. The resource persons were leading foreign experts from different countries i.e., China, New Zealand, Italy, USA, and Pakistan. While 32 posters were presented on various themes of pandemics and epidemics in the Poster competition, in which young scientists from across the country participated. Over 400 academicians, scientists, researchers, and postgraduate students from Pakistan and abroad have registered to participate in the deliberations of the conference through physical and/or virtual (online) presence. In addition to the technical sessions, four group works were conducted to formulate recommendations. Recommendations of the conference will be shared with national and international bodies and research institutions dealing with the development of vaccines for the control of potential epidemic and pandemic-related issues worldwide.